Effect of roughness parameters on performance of solar air heater having artificial wavy roughness using CFD. (January 2022) - Haldar, Ankur; Varshney, L.; Verma, Prashant
Abstract: The current study used Ansys FLUENT software to perform a computational fluid dynamics analysis of a solar air heater with artificial wavy roughness. Roughness elements were studied for twelve wavy surface configurations with rib heights ( e ) of 0.7 mm, 1 mm, and 1.4 mm and pitch ( p ) of 10, 15, 20, and 25 mm. A 2D computational domain is modelled and the involved differential equations are solved using a finite volume method. To solve the transport equations for turbulent flow and energy dissipation rate, the RNG k-ε turbulence model with enhanced wall function is employed. For a uniform heat flow of 1000 W/m 2, the effect of roughness parameter on Nusselt number, friction factor, and thermo-hydraulic performance parameter (THPP) is investigated. On the basis of the THPP, the best geometric parameter values are found in the Reynolds Number ( Re) range of 3800–18, 000. At Re of 12, 000, the optimal THPP is 1.96, which corresponds to a rib height of 0.7 mm and a pitch of 15 mm.